Pengembangan Student Book of Circulatory System dengan Integrasi Pendidikan Karakter untuk Siswa Kelas XI Rintisan SMA Bertaraf Internasional - HAVIAH HAFIDHOTUL I (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
The Application of character education is one of Government’s policies to prevent several moral’s problems and draw up young generations so that they are able to compete in globalization era. This policy has been started to be applied in schools, including RSMABI. However, there is so difficult to find student book that was integrated with character education, whereas it is very important to apply the character education. Based on the condition, a research to develop student book of circulatory system which was integrated with character education has been done. The objective of this research is to obtain the student book of circulatory system which was integrated with character education for grade XI of RSMABI. This research used 4D model without disseminaton step, because research time was limited. The criteria to define the student book’s feasibility are it’s material, performance, language, and accuracy of character value that were integrated. The student book has been reviewed by some reviewers that were consisted of biology lectures and high school teachers. The result of this research shows that the student book of circulatory system’s feasibility was categorized good. Keywords: development, student book, character education, circulatory system.